Affordances of Augmented Reality Systems for Co-Located Collaboration - Schopf, Peter; Jonas, Julia (Proceedings of the 56th Hawaii International Conference on System Sciences, 2023)
This paper aims to identify relevant affordances towards an augmented reality system for organizational practices of co-located collaboration. As augmented reality is a means to visualize and author information, such an artifact could enable intuitive sharing of information. It can be shown that single aspects are reflected in literature, missing so far is a comprehensive description of relevant affordances for such an artifact. The concept of affordances is increasingly used in information research, as it enables to define design principle based on the action goals of the user. Addressing the lack of clear formulation guidelines of affordances, a proposal is presented of how affordances can be formulated to reduce uncertainty and ambiguity. This paper makes two major contributions: (1) it introduces how augmented reality systems can contribute to organizational practices of co-located collaboration and (2) illustrates how affordances can be utilized to derive requirements for such systems from interviews.
Keywords: Design; Development; and Evaluation of Collaboration Technologies; affordances; augmented reality systems; collaboration